What's so funny? - Westlake, Donald E. (Westlake, Donald E. Dortmunder series., 2007)
Tempted to find a highly valuable, seven-hundred-pound chess set, hapless crook John Dortmunder musters his merry band of fellow ne'er-do-wells on a haphazard treasure hunt that prompts his investigation of Russia's last czar.